Studies of Bs2∗(5840)0 and B s 1(5830) 0 mesons including the observation of the Bs2∗(5840)0→B0KS0 decay in proton-proton collisions at √s=8TeV - Sirunyan, A. M. (2018)
Measurements of Bs2∗(5840)0 and B s 1(5830) 0 mesons are performed using a data sample of proton-proton collisions corresponding to an integrated luminosity of [InlineEquation not available: see fulltext.], collected with the CMS detector at the LHC at a centre-of-mass energy of 8TeV. The analysis studies P-wave Bs0 meson decays into B (∗) +K - and B(∗)0KS0, where the B + and B 0 mesons are identified using the decays B +→ J / ψK + and B 0→ J / ψK ∗(892) 0. The masses of the P-wave Bs0 meson states are measured and the natural width of the Bs2∗(5840)0 state is determined. The first measurement of the mass difference between the charged and neutral B ∗ mesons is also presented. The Bs2∗(5840)0 decay to B0KS0 is observed, together with a measurement of its branching fraction relative to the Bs2∗(5840)0→B+K- decay.